Assessment of the social sustainability of public housing projects in Chile - Sierra-Varela, Leonardo; Rivas-Ríos, Francisco (Revista Ingeniería de Construcción, 2024)
The consideration of qualitative social approaches in public housing projects is not clear in the implementation process. Public agencies lack processes incorporating explicit social criteria for assessing public housing projects. Therefore, the inclusion of social sustainability in early planning and decision-making is limited. This study presents a structural model explaining the fundamental interdependence of social criteria that govern socially sustainable housing projects for vulnerable populations in Chile. For this purpose, a theoretical structural equation model (SEM) was constructed, derived from the application of a survey administered to 188 professionals involved in public housing development. In addition, the model was validated through five public housing projects in the Araucanía Region and compared with other survey methods. A model of ten criteria and 33 indicators was obtained. The results are consistent with other social certification methods (ENVISION and CVS). However, factors such as improvement in family economic capacity, housing committee involvement, and neighborhood functional integration are significant and not included in other approaches